Hubungan Penerapan Triase Berdasarkan Emergency Severity Index dengan Peningkatan Mutu Pelayanan IGD Rumah Sakit Sari Asih Cipondoh - Doni Reva Setiadi (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
The Emergency Room (ER) is a hospital service unit that plays a strategic role in treating patients with critical and emergency conditions. The high number of patient visits and limited resources require an effective triage system to ensure quality of service and patient safety. The Emergency Severity Index (ESI) is a five-level triage system that classifies patients based on the level of severity and resource requirements. This study aims to analyze the relationship between the implementation of triage based on the Emergency Severity Index and the improvement of EAD service quality at Sari Asih Cipondoh Hospital. This study used a quantitative design with a cross-sectional approach. The study sample consisted of EAD patients who met the inclusion criteria. Data were collected through observation of triage implementation and patient satisfaction questionnaires, then analyzed using univariate and bivariate analysis. The results showed that the proper implementation of ESI triage was significantly associated with improved quality of ED services, particularly in terms of speed of service and patient satisfaction. The conclusion of this study confirms that the implementation of ESI triage is an important factor in efforts to improve the quality of ED services.